RELIABILITY-BASED MAINTENANCE STRATEGY FOR A MILITARY WEAPON SYSTEM – A CASE STUDY - Chambel, Enio; Gonçalves, Paula; Ferreira, Luís Andrade (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Military Weapons Systems are currently facing increasing use in a worldwide intensification of military conflicts, leading to various changes to improve and solve problems in logistics operations. The main objective of this paper is to use RCM (Reliability Centered Maintenance) and FMECA (Failure Modes, Effects, and Criticality Analysis) methodology applied to this High-Tech Weapon System to identify the need for spare parts by improving the current maintenance plan. A functional analysis was performed. Then, functional failures, failure modes, and effects are defined. This methodology manages the identified risks, knowing which components have a high failure rate, improving maintenance plans, and identifying the need for spare parts at the earliest possible stage. Thus, the study was supported by “ReliaSoft RCM++” software that facilitates the RCM analysis approach. This software supports all major RCM industry standards such as ATA, MSG-3, MIL-STD-1629A, SAE JA1011, and SAE JA1012 and provides complete capabilities for FMECA. This study aims to identify the systems, subsystems, and components that frequently fail, ensuring operational capability and corrective actions to improve the weapon system’s plans, maintenance schedules, and availability. This technique is powerful as decision support to the Military Logistics Command because it identifies the need for spare parts as early as possible.